Efeitos da dupla tarefa em variabilidades de marchas em idosos - Souza, Felipe Heylan Nogueira de (2018)
Objective: To investigate the deterioration of gait in different conditions associated with cognitive planning in healthy elderly. Methods: This is a cross-sectional study involving 17 elderly women with age between 60-75 years (66.00 ± 4.67). Individuals were clinically described by the following instruments: Dynamic Gait Index, Berg Balance Scale, Mine Mental State Examination and Leganés Cognitive Test. The experimental protocol consisted of performing the three cognitive tasks of the Stroop test - Word (Pal), Color (Co) and Word-Color (Pal-Co) - during four gait conditions: treadmill gait (TR), ground gait without disturbance (GR), straight ground gait with disturbances (GRGD), and ground gait at eight (GG8). Each task was performed three times, with duration of 20 seconds and intervals of three minutes. The kinematic variables, number of steps (NS), cadence (Ca) and velocity (VL) was collected through with pressure sensors on the treadmill for TR, was collected through with pressure sensors on the treadmill for TR, and sensors Foot Switch fixed in soles in the GR, GRGD and GG8. The normality of the data was analyzed and the one-way ANOVA and Pearson's correlation were used through SPSS 2.0 software. Results: The cognitive tasks of the Stroop test presented a deterioration in the final score of the test, presenting a significant effect of the reduction of number of Words and number of Colors (p <0.05) in all conditions when compared TR (Pal 33 , 78 ± 6.31, Co 23.19 ± 5.78) to GR (Pal 26.76 ± 6.59, Co 16.84 ± 5.55), GG 8 (Pal 25.72 ± 6.53; 15,17 ± 5,76) and GRGD (Pal 22,94 ± 7,22, Co 16,11 ± 6,00), whereas for word color there was a significant effect on the reduction in the number of items (p <0, 05) only when compared TR (13.58 ± 3.16) to GRGD (9.88 ± 3.50) and GG 8 (9.84 ± 3.50). When comparing the cost of the Stroop task in the steps and cadence in ME wit a different conditions ground gait , a significant change in gait observed from the usual to the slower (p <0.05), already in soil situations only the GR x GG8 demonstraram haver essas diferenças (p> 0.05), whereas the cadence was not significant in color item in soil situations (p>0,05), for the words item there was a change in the score only between GR x GR8 (p<0,05), and for the item Words-Color there was significance between GR x GRGD and GR x GR8 (p> 0.05). Conclusion: The findings suggest that the cognitive task during gait variability was altered, suffering a negative impact as the load was increased, and that patterns of gait kinematics produced different measures in the steps and cadence being larger viewed only between revolving activities.